DECISION SUPPORT SYSTEM FOR DETERMINING THE PRIORITY OF FACILITY AND INFRASTRUCTURE REPAIRS AT SMP NEGERI 1 BAKI USING THE WEIGHTED PRODUCT METHOD - Wupiwulang Tanwal Hu; Dwi Hartanti; Aprilisa Arum Sari (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2025)
The condition of educational facilities and infrastructure significantly influences the effectiveness of the teaching and learning process. At SMP Negeri 1 Baki, the process of determining which facilities require priority repairs is still carried out manually, which leads to inefficiencies and subjective decision-making. This study aims to implement a Decision Support System (DSS) that can assist school administrators in determining the priority of facility and infrastructure improvements using the Weighted Product (WP) method. The WP method is chosen because it can process multiple criteria by assigning weighted values to each one, enabling a more objective and accurate assessment. The criteria used include the level of damage, frequency of use, number of users, and impact on learning activities. The system is developed in a web-based format to facilitate accessibility and ease of use. The results of this study show that the application of the WP method in the DSS effectively assists decision-makers in ranking the priority of improvements based on accurate data. This research is expected to improve the efficiency, transparency, and accountability of maintenance planning in educational institutions.